On the edge of Prehistory. Preliminary results of excavations at three Chalcolithic and Bronze Age sites in southern Jordan - Piotr Kołodziejczyk; Marek Nowak; Michał Wasilewski; Barbara Witkowska; Jacek Karmowski; Marcin Czarnowicz; Justyna Zakrzeńska; Agnieszka Brzeska-Zastawna (Polish Archaeology in the Mediterranean)
This article summarizes the research conducted between 2019 and 2022 by a Jagiellonian University (JU) team at three important sites in southern Jordan: Umm Tuweyrat, Wadi Quseir/Huseiniya, and Wadi Faynan 731. The data gathered provide new perspectives on population groups inhabiting the southern part of modern Jordan during Late Prehistory and give insights provoking reconsiderations of previous assumptions. The excavated sites offer new vantage points on the human presence in this area, illustrating the everyday life of these communities and elements of their spiritual culture, as well as their intriguing relationships with the surrounding landscape. The Umm Tuweyrat site is a dolmen field shedding light on spirituality and family traditions. A recent analysis preliminarily dates these structures within the Bronze Age. The other two sites represent settlement and farming traditions and are preliminarily dated to the transition period between the Chalcolithic and the Early Bronze Age.